KONFLIK PERAN GANDA IBU RUMAH TANGGA BURUH PENGUPAS BAWANG MERAH DI PASAR INDUK KRAMAT JATI JAKARTA - devi, sonia; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
The advancement of the times has opened opportunities for housewives to work and take on dual roles in both the domestic sector (household) and the public sector (employment), including housewives working at Pasar Induk Kramat Jati Jakarta. This study aims to analyze how housewives who work as shallot peelers at Pasar Induk Kramat Jati Jakarta balance their roles between family and work, as well as the impact of role conflict on them. This research uses a descriptive qualitative approach with observation and interviews as data collection techniques. The theoretical framework used is the work-family conflict theory by Greenhaus & Beutell (1985), which identifies three types of conflict: time-based conflict (difficulty in time allocation), strain-based conflict (physical and mental fatigue), and behavior-based conflict (inability to adjust behavior appropriately). The results show that these housewives manage their dual roles by completing household tasks before heading to the market, but they still face difficulties in dividing time between family and work. The study also reveals the effects of role conflict and how the work-family conflict theory is relevant to the experiences of these women. Time-based conflict is reflected in being late to work and having little time for their children and themselves. Strain-based conflict includes physical exhaustion, chronic stress, and excessive anxiety. Behavior-based conflict manifests in disharmonious relationships with their children and husbands. It is recommended that the participants maintain their physical and mental health, seek social support, and wear protective glasses while peeling shallots to reduce eye irritation.